2007 4th Annual IEEE Communications Society Conference on Sensor, Mesh and Ad Hoc Communications and Networks 2007
DOI: 10.1109/sahcn.2007.4292841
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation of IEEE 802.15.4 Transmission Power Control and Interference Minimization

Abstract: Abstract-Although the characteristics of RF transmissions are physically well understood at the lowest levels of communication design, accurately incorporating power and interference effects is one of the most challenging tasks in designing efficient wireless network algorithms. The most noteworthy approaches are the circular transmission and interference "ranges" that do not apply to antennae packages that are not omnidirectional, as well as to non line-of-sight environments of many low power wireless sensor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 15 publications
1
11
0
Order By: Relevance
“…Similar results to [75] were obtained; PLR at the receiver increased with the increase of the signal power of the interfering node, and decreased with the increase in the channel spacing. Further, it was shown that interference has larger impact on large packet sizes, this is due to the higher collision and packet error probabilities.…”
Section: Coexistence Issues In Wban Technologiessupporting
confidence: 84%
See 4 more Smart Citations
“…Similar results to [75] were obtained; PLR at the receiver increased with the increase of the signal power of the interfering node, and decreased with the increase in the channel spacing. Further, it was shown that interference has larger impact on large packet sizes, this is due to the higher collision and packet error probabilities.…”
Section: Coexistence Issues In Wban Technologiessupporting
confidence: 84%
“…They have palpable impact in testbed scenarios as compared to simulation and mathematical modeling. The antenna orientation, mobility of nodes, and the human body Packet size [11,67,75,91,98] Physical layer modulation scheme [30,70] Receiver type [30] Nodes mobility and human body [23] [ 23, 25,42] Wireless Netw effect have not been studied mathematically. Moreover, many analytical modeling studies considered SIR more than frequency spacing.…”
Section: Summery and Discussionmentioning
confidence: 99%
See 3 more Smart Citations